2020
DOI: 10.1177/0300060520926349
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of statin treatment based on cardiovascular outcomes in elderly patients: a standard meta-analysis and Bayesian network analysis

Abstract: Objective Statins have been shown to be beneficial for the prevention of cardiovascular events. In elderly individuals, the efficacy of statins remains controversial and the comparative effect of statins has not been assessed. Methods MEDLINE, Embase, and the Cochrane Central database were searched for randomized controlled trials that assessed statins in older patients. Results Seventeen trials were analyzed. When used for secondary prevention, statins were associated with reduced risk of cardiovascular event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
(273 reference statements)
1
7
0
Order By: Relevance
“…The substantial statin benefits obtained for secondary prevention closely match the findings of Ponce et al for ASCVD events and mortality rate. Also in agreement with Ponce et al, in primary prevention statins were observed to significantly reduce the rate of myocardial infarction but not all-cause or cardiovascular mortality [ 76 ]. Despite this abundance of evidence from RCTs, two retrospective propensity score-matched studies in narrow populations recently reported reductions in all-cause mortality/ASCVD events in primary prevention adults aged 75+.…”
Section: Efficacy Of Statin Treatment In the Elderlysupporting
confidence: 87%
See 1 more Smart Citation
“…The substantial statin benefits obtained for secondary prevention closely match the findings of Ponce et al for ASCVD events and mortality rate. Also in agreement with Ponce et al, in primary prevention statins were observed to significantly reduce the rate of myocardial infarction but not all-cause or cardiovascular mortality [ 76 ]. Despite this abundance of evidence from RCTs, two retrospective propensity score-matched studies in narrow populations recently reported reductions in all-cause mortality/ASCVD events in primary prevention adults aged 75+.…”
Section: Efficacy Of Statin Treatment In the Elderlysupporting
confidence: 87%
“…In 2020, a meta-analysis was performed based on 17 RCTs in elderly patients 65+ for primary or secondary prevention [ 76 ]. The substantial statin benefits obtained for secondary prevention closely match the findings of Ponce et al for ASCVD events and mortality rate.…”
Section: Efficacy Of Statin Treatment In the Elderlymentioning
confidence: 99%
“…As for most preventive drugs in cardiovascular disease, the evidence underpinning recommendations for secondary prevention of stroke is weaker in patients aged 75 years or more. Several analyses though, have indicated that the preventive effects seem to be as good in the elderly as in younger patients 21. Most international and national guidelines thus, do not discern patients based on age.…”
Section: Discussionmentioning
confidence: 99%
“…Several analyses though, have indicated that the preventive effects seem to be as good in the elderly as in younger patients. 21 Most international and national guidelines thus, do not discern patients based on age.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 In congruence with this, a meta‐analysis of 17 statin trials found statin treatment to reduce the risk of all‐cause mortality and recurrent stroke. 18 …”
Section: Discussionmentioning
confidence: 99%